Regionalized nervous system in Hydra and the mechanism of its development - Noro, Yukihiko; Yum, Seungshic; Nishimiya-Fujisawa, Chiemi; Busse, Christina; Shimizu, Hiroshi; Mineta, Katsuhiko; Zhang, Xiaoming; Holstein, Thomas W.; David, Charles N.; Gojobori, Takashi; Fujisawa, Toshitaka (Gene expression patterns, 2019)
The last common ancestor of Bilateria and Cnidaria is considered to develop a nervous system over 500 million years ago. Despite the long course of evolution, many of the neuron-related genes, which are active in Bilateria, are also found in the cnidarian Hydra. Thus, Hydra is a good model to study the putative primitive nervous system in the last common ancestor that had the great potential to evolve to a more advanced one. Regionalization of the nervous system is one of the advanced features of bilaterian nervous system. Although a regionalized nervous system is already known to be present in Hydra, its developmental mechanisms are poorly understood. In this study we show how it is formed and maintained, focusing on the neuropeptide Hym-176 gene and its paralogs. First, we demonstrate that four axially localized neuron subsets that express different combination of the neuropeptide Hym-176 gene and its paralogs cover almost an entire body, forming a regionalized nervous system in Hydra. Second, we show that positional information governed by the Wnt signaling pathway plays a key role in determining the regional specificity of the neuron subsets as is the case in bilaterians. Finally, we demonstrated two basic mechanisms, regionally restricted new differentiation and phenotypic conversion, both of which are in part conserved in bilaterians, are involved in maintaining boundaries between the neuron subsets. Therefore, this study is the first comprehensive analysis of the anatomy and developmental regulation of the divergently evolved and axially regionalized peptidergic nervous system in Hydra, implicating an ancestral origin of neural regionalization.